Comment: Non-invasive prediction of post-sustained virological response hepatocellular carcinoma in hepatitis C virus - Miao, Xinpu; Wu, Haidong; Xu, Jinrong; Cheng, Wei (Clinical and molecular hepatology, 2025)
KCI Citation Count: 0